Analisis Kebijakan Badan Pengelola Perbatasan Daerah Terhadap Permasalahan Illegal Fishing di Wilayah Perbatasan Kepri - Adellia Adellia; Khairun Nisa Siregar; Yesi Juliantri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This journal analyzes the policies implemented by the Regional Border Management Agency (BPPD) regarding the problem of illegal fishing in the border area of the Riau Islands (KEPRI). Illegal fishing is a serious challenge faced by Indonesia and other archipelagic countries. The results of the analysis show that the BPPD has implemented various policies to address the problem of illegal fishing in the KEPRI border area. These policies include cooperation with related agencies, stricter law enforcement, and strengthening the capacity of local communities in managing marine resources. Based on the results of the analysis, this study recommends the need to strengthen inter-agency collaboration in law enforcement and maritime surveillance in the KEPRI border area. In addition, it is also important to increase public education and awareness about the importance of maintaining the sustainability of marine resources and involve them in the management of these resources.